2018
DOI: 10.15171/ijhpm.2018.107
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Acute Conflict and Maternal Care Usage in Egypt: An Uncontrolled Before-and-After Study Using Demographic and Health Survey Data

Abstract: Background: United Nations’ (UN) data indicate that conflict-affected low- and middle-income countries (LMICs) contribute considerably to global maternal deaths. Maternal care usage patterns during conflict have not been rigorously quantitatively examined for policy insights. This study analysed associations between acute conflict and maternal services usage and quality in Egypt using reliable secondary data (as conflict-affected settings generally lack reliable primary data). Methods: An uncontrolled before-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Much of the failure to achieve the health goals set by the World Health Organization in third world countries is attributed to different kinds of crises. During a political or health crisis, women are less likely to seek health care [ 14 , 15 ]. In 2003 in Hong Kong following the SARS epidemic, 75 % of the population reported that they refrained from medical examination due to fear of infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the failure to achieve the health goals set by the World Health Organization in third world countries is attributed to different kinds of crises. During a political or health crisis, women are less likely to seek health care [ 14 , 15 ]. In 2003 in Hong Kong following the SARS epidemic, 75 % of the population reported that they refrained from medical examination due to fear of infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, conflict-affected low- and middle-income countries (LMICs) have been associated with poorer maternal and child health (MCH) outcomes [ 3 ]. It was reported that out of the 34 LMICs furthest from achieving global MCH targets, 22 were identified as conflict-stricken countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 Conversely, other sources have shown limited associations between conflict and maternal health indicators, such as antenatal care and institutional deliveries. 23,24 Further research is needed to document the mechanisms through which conflict influences mortality in C-sections. 25 A previous study reported that the barriers to accessing health care in Afghanistan were associated with a higher number of maternal deaths compared with women who died from non-maternal causes.…”
Section: Discussionmentioning
confidence: 99%